Editorial - Viáfara González, John Jairo (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The Master Program in Language Teaching at Universidad Pedagógica y Tecnológica de Colombia (UPTC) has published the Enletawa Journal for the last eight years. The publication invested in the dissemination of academic work in applied linguistics and in fields associated with scientific and aesthetic perspectives to the study of languages. During this time, our journal has undergone several transformations which signals its constant efforts to adapt to the increasing demands posed by information technology advances,  national and international research agencies and an audience whose academic specialization is rapidly increasing.One recent innovation in our journal is the editorial committee’s decision to make of Enletawa a biannual publication starting with this issue. This change in our journal´s publication frequency seeks to increase its visibility and to allow for its faster distribution to our readers. In preparation for the new challenge that biannual publication implies we have invited more of our colleagues to join in our journal´s endeavors. It is a pleasure to welcome Colombian professors: Camen Helena Guerrero (Universidad Fracisco José de Caldas) to the Editoral Committee and Lisseth Rojas (Universidad Surcolombiana), Jairo Enrique Castañeda (Universidad de la Salle), Alexandra Botero, (Universidad Pedagógica Nacional), Yakelin Salinas (Fundacion Universitaria Los Libertadores), Leidy  Marcela Chacón, Fredy Alonso Dueñas Macías, Martha Pardo Segura, (UPTC) to the Editorial Review Board. Additionally, several international professors have accepted our invitation to become part of the journal scientific committee. They include: Igbak Abdul Oader Al Balushi (College of Applied Sciences, Oman), Trudie Clarck McEvoy (University of Arizona, USA), Denise M. Osborne (University at Albany, Suny, USA), A.G. Rud (Washington State University, USA) and Brian G. Hibbs (Dalton State College, USA) as part of the Scientific Committee. We greatly appreciate the support of all our new committee members.   The collection of articles included in this issue includes four research articles and two reflective papers. The first research paper shares a study conducted by Javier Díaz and Carlos Ernesto Duran. Their article, “The collaborative portfolio: Exploring reading skills through peer tutoring” emerges from their undergraduate final research paper and focuses on their experience as peer-tutors in a public university research group. Duran and Díaz study describes how portfolios became a mediation tool to leverage the tutoring relationship established between them and their tutees to foster these first semester students’ reading skills. The second article, “De petits promoteurs de la vie saine » des émissions de radio pour entendre, se faire entendre et apprendre le français”, also originated from authors´ undergraduate final research work. Manuel Fernando Dimas, Nadia Carolina Alezones and Henry Ernesto González examine the impact that recorded radio transmissions have on third graders development of French oral skills. Their study exemplifies possible curricular interconnections between French and other school subjects which can become powerful strategies to leverage young students´ language learning.             Two rural schools are the sites where the last two research studies included in this issue were conducted. Julie Natalie Parra explored how Chevano tenth graders restory their resilience experience after a natural disaster in their hometown.  By using narratives as a pedagogical design and part of her research approach, the author determined that storying allowed participants to “look themselves in the mirror” and to “dare themselves”, meaning that they expressed hope despite the adverse circumstances they had lived. In her article, “Blogging as an EFL practice beyond the classroom”, Rosa María Amado shares her findings concerning students’ English learning by means of this web 2.0 application in rural Boyacá. Her study informs us about teachers efforts to keep abreast in the use of pedagogical resources despite the challenges that geographical location can pose. Closing our first biannual issue, Enletawa Journal features two reflective articles. The main characters in Miguel Angel Sanabria´s manuscript are student teachers in a “Escuela Normal” in Boyacá. The prospective teachers participated in a peer-editing cycle designed by Sanabria under the principles of process writing and formative assessment. In addition to illustrating how the author conceived and implementing the model, the article reveals his considerations regarding participants’ views about their English writing development. Our second article in French, “L’éloignement de la famille :repartir à zérovers le vide”, written by Carolina Sierra Díaz, focuses on her analysis of three novels: Disgrace  J.M Coetzee (2008), The Trial  Franz Kafka (1983), The Human Stain Philip Roth (2000) and Mon cœur à l’étroit Marie Ndiaye (2007). Specifically Sierra discusses detachment, debt transmission and silent suffering in families as themes to guide alternative readings of these novels. The editor, editorial and scientific committees, and review board of Enletawa Journal welcome you to our first biannual issue. The journal is always inspired by our growing audience that guides the decisions we are constantly making to increase the quality of our publication. We are sure this new issue will generate plenty of scholarly reflection in our readers. John Jairo Viáfara GonzálezEditor